Activation of the IL-1β/KLF2/HSPH1 pathway promotes STAT3 phosphorylation in alveolar macrophages during LPS-induced acute lung injury. Issue 3 (4th March 2020) - Liang, Yafeng; Luo, Jiaqi; Yang, Nengli; Wang, Shufen; Ye, Mingwei; Pan, Guoquan
Abstract: Acute lung injury (ALI) is a lethal disease with diffuse lung inflammation, in which JAK/STAT3 signaling has been well recognized for its role in initiating and amplifying inflammatory processes. However, the mechanism for the enhancement and maintenance of signal transducer and activator of transcription 3 (STAT3) activation has not yet been clearly demonstrated in ALI. In the present work, we established a lipopolysaccharide (LPS)-induced ALI rat model through intratracheal instillation and isolated the alveolar macrophages (AMs) from the rats in the model. We demonstrated that the expression of Kruppel-like factor 2 (KLF2) significantly decreased in the AMs from LPS-induced ALI rats (LPS-AMs) as compared with the AMs from control rats (NC-AMs). Overexpressing KLF2 in LPS-AMs inhibited the phosphorylation of STAT3 and reduced the levels of STAT3 target genes, including matrix metalloproteinase (MMP)-2/9 (MMP-2/9). Further investigation indicated that KLF2 trans-inhibited heat shock protein H1 (HSPH1), which interacted with STAT3 and enhanced its phosphorylation. As a crucial inflammatory mediator in ALI, interleukin-1β (IL-1β) induced the down-regulation of KLF2 in LPS-AMs, as interrupting IL-1β signaling in LPS-AMs by antibody neutralization or IL1R1 knockdown rescued the expression of KLF2. Consistently, stimulating NC-AMs with IL-1β decreased KLF2 and increased HSPH1, while overexpression of KLF2 suppressed IL-1β-induced HSPH1. Additionally, in vivo studies showed that treatment with an IL-1β antibody or HSPH1 inhibitor alleviated lung injury in ALI rats, as well as decreased the levels of p-STAT3 and MMP-2/9. In conclusion, activation of the IL-1β/KLF2/HSPH1 pathway facilitated STAT3 phosphorylation in AMs, which exacerbated pulmonary inflammation in ALI.